The Document On Human Fraternity For World Peace and Living Together: Perlawanan Terhadap Terorisme dan Komitmen pada Perdamaian Dunia - Meo, Reinardus L; Timur, Fauzia Gustarina Cempaka; Afifuddin, Moch (Institut Filsafat dan Teknologi Kreatif Ledalero, 2024)
The purpose of this article is to elucidate and promote the key points of the Document on Human Fraternity for World Peace and Living Together. This historic document, signed in Abu Dhabi by Pope Francis and Grand Imam of Al-Azhar Ahmad Al-Tayyeb, emphasizes human brotherhood for world peace and coexistence. This grand and magnificent agenda sidesteps a number of significant challenges, including terrorism. Terrorism is viewed as a threat that must be condemned in all of its manifestations. Terrorism is a global offense that threatens international peace and security. Therefore, resistance is required. This resistance is the responsibility of more than a few stakeholders. This article intends to demonstrate a commitment to world peace by combating terrorism through the use of qualitative research techniques, literature studies, and other sources. The Document on Human Fraternity calls on all believers to unite in the struggle against terrorism and for global peace. Keywords: Human Fraternity, Humanity, Peace, Terrorism, World Peace